Kalimatun Sawa’ as The Basis of Religious Tolerance (Interpretation of Nurcholish Madjid’s Thoughts Based on Paul Ricoeur’s Hermeneutics) - Haryati, Tri Astutik; Zuhri, Amat; Marom, Naelil (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2020)
This paper aims to understand Nurcholish Madjid’s thoughts deeply on kalimatun sawa’ as thefoundation of religious tolerance. The study employs Paul Ricoeur’s hermeneutic approach with a qualitativeresearch method, focusing on textual analysis of Madjid’s works. The main issues examined include theinterpretation theory in Paul Ricoeur’s hermeneutics, Nurcholish Madjid’s perspective on kalimatunsawa’, and the application of Ricoeur’s hermeneutic theory in understanding kalimatun sawa’. Thefindings indicate that kalimatun sawa’ serves as a universal ethical foundation for interfaith dialogue,emphasizing shared human values fostering religious tolerance in Indonesia. This study contributes to theacademic discourse by offering a novel application of Ricoeur’s hermeneutic approach in Islamic studies,providing a deeper interpretative framework for understanding religious pluralism.